2007
DOI: 10.1007/s00381-007-0428-0
|View full text |Cite
|
Sign up to set email alerts
|

The pediatric Chiari I malformation: a review

Abstract: Appropriate literature germane to the CIM is reviewed and discussed. There is variation in the reported anatomy, outcome, and treatment for children with CIM. Based on the literature, most patients have preoperative symptoms or findings (e.g., syringomyelia) improve no matter what surgical technique is utilized. However, standardized treatment paradigms based on randomized controlled studies are still necessary to elucidate the optimal selection and treatment criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
126
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(127 citation statements)
references
References 118 publications
1
126
0
Order By: Relevance
“…Herniations with a length of tonsilla cerebelli expanding from the level of the foramen magnum to the canalis vertebralis > 3 mm were considered to be CMI (22)(23)(24)(25).…”
Section: Measurements Of the Tonsillar Herniation The Posterior Heigmentioning
confidence: 99%
“…Herniations with a length of tonsilla cerebelli expanding from the level of the foramen magnum to the canalis vertebralis > 3 mm were considered to be CMI (22)(23)(24)(25).…”
Section: Measurements Of the Tonsillar Herniation The Posterior Heigmentioning
confidence: 99%
“…less often include occipitocervical instability and acute postoperative hydrocephalus. 5,9,24 As a result of these complications, many surgeons have moved toward less invasive surgical treatments such as "extradural decompression" alone, which involves bony decompression plus or minus thinning or splitting of the dura without actually entering the intradural space. 6,7,17,20,29 The theoretical advantages associated with this less invasive technique include reduced operative times, lower rates of CSF leakage and postoperative complications, and reduced postoperative hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…19 Surgical decompression of CM-I is often recommended in symptomatic patients with CSF obstruction, as it has been shown to improve the clinical course of these patients. 21,24 While multiple surgical treatment strategies have been described in the literature, the most common procedure currently performed is posterior fossa decompression, which consists of a suboccipital craniectomy and C-1 laminectomy, with duraplasty. 12 Multiple previous studies have reported a range of complications associated with surgical management of CM-I (range 3%-40%).…”
Section: ©Aans 2013mentioning
confidence: 99%
“…These include visual disturbances, dysphonia, dysphagia, sleep apnea, clumsiness and incoordination, and sensory disturbances. 128,129 CM may also lead to the development of syringomyelia, which, in turn, may lead to other symptoms including motor and sensory difficulties, pain, and scoliosis. [130][131][132][133][134] Surgical case series tend to overestimate the frequency of syringomyelia in patients with CM.…”
Section: Chiari and Syringomyeliamentioning
confidence: 99%